2018
DOI: 10.2196/jmir.9499
|View full text |Cite
|
Sign up to set email alerts
|

A Single-Session, Web-Based Parenting Intervention to Prevent Adolescent Depression and Anxiety Disorders: Randomized Controlled Trial

Abstract: BackgroundDepression and anxiety disorders are significant contributors to burden of disease in young people, highlighting the need to focus preventive efforts early in life. Despite substantial evidence for the role of parents in the prevention of adolescent depression and anxiety disorders, there remains a need for translation of this evidence into preventive parenting interventions. To address this gap, we developed a single-session, Web-based, tailored psychoeducation intervention that aims to improve pare… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
64
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(72 citation statements)
references
References 98 publications
(124 reference statements)
5
64
2
1
Order By: Relevance
“…We used a modified version of the Brief Spence Children's Anxiety Scale and were unable to locate Australian data to directly compare our data. We compared depressive symptoms in our sample to one previous Australian study of 349 children aged 12-15 years, but did not find any differences (Cardamone-Breen et al, 2018). This may be positive and suggest that there is no increase in depression in young adolescents during the pandemic.…”
Section: Covid-19 and Increased Mental Health Risksmentioning
confidence: 71%
See 1 more Smart Citation
“…We used a modified version of the Brief Spence Children's Anxiety Scale and were unable to locate Australian data to directly compare our data. We compared depressive symptoms in our sample to one previous Australian study of 349 children aged 12-15 years, but did not find any differences (Cardamone-Breen et al, 2018). This may be positive and suggest that there is no increase in depression in young adolescents during the pandemic.…”
Section: Covid-19 and Increased Mental Health Risksmentioning
confidence: 71%
“…We compared our CPAS findings to four studies with pre-pandemic data available on our key parent and child outcomes measures. We compared to Australian published data on parent mental health for 497 parents aged 18-86 years with a dependent child (Crawford, Cayley, Wilson, Lovibond, & Hartley, 2011), and on parent-report of child depression for 349 children aged 12-15 years (Cardamone-Breen et al, 2018). To compare other parent and family outcomes, we also analyzed original data from two additional studies.…”
Section: Pre-pandemic Australian Datasetsmentioning
confidence: 99%
“…The average number of participants across studies was n = 208.60, and ranged broadly from 33 to 916 participants. Male youth were well represented across many studies, constituting more than 50% of the young people in 14 studies (Baker et al, ; Cardamone‐Breen et al, ; DuPaul et al, ; Enebrink et al, ; Hinton et al, ; Irvine et al, ; Jones et al, ; Morawska et al, ; Sanders et al, ; Sanders et al, ; Sourander et al, ; Van Zeijl et al, ; Yap et al, ), on average making up 44.6% of youth participants. In contrast, male caregivers were severely underrepresented (on average 5.0%), with only three studies including more than 10% male caregivers (Khanna et al, ; MacKenzie & Hilgedick, ; Yap et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…No male caregivers were primary recipients of the intervention in eight studies (Breitensteinet al, 2016; Fang et al, 2010; Hemdi & Daley, ; Sanders et al, ; Schinke et al, ; Schinke et al, ; Schwinn et al, ; Van Zeijl et al, ). In most studies, the majority (>50%) of the sample were educated with post‐secondary qualifications ( n = 14, Baker et al, ; Cardamone‐Breen et al, ; Day & Sanders, ; DuPaul et al, ; Fang et al, ; Hemdi & Daley, ; Jones et al, ; Khanna et al, ; Morgan et al, ; Sanders et al, ; Sanders et al, ; Schinke et al, ; Schinke et al, ; Schwinn et al, ; Yap et al, ). While most studies did not adequately report the employment status of their participants ( n = 14, DuPaul et al, ; Enebrink et al, 2012; Fang et al, ; Khanna et al, ; Kuravackel et al, ; MacKenzie & Hilgedick, ; Morawska et al, ; Morgan et al, ; Nixon et al, ; Sanders et al, ; Schinke et al, ; Schinke et al, ; Schinke et al, 2009b; Sourander et al, ; Van Zeijl et al, 2006), of those that did, most reported over 50% of their sample engaged in employed work of some description ( n = 8, Baker et al, ; Cardamone‐Breen et al, ; Day & Sanders, ; Hinton et al, ; Irvine et al, ; Sanders et al, ; Schwinn et al, ; Yap et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation